2019
DOI: 10.1097/mao.0000000000002370
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Bone Conduction Hearing Implants in Patients With Bilateral Microtia-atresia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
2
21
0
4
Order By: Relevance
“…The incidence of post-operative pain also has been reported as relatively low for the BCI601 [32], such complaints were not reported in our cohort, neither for the BCI601 nor for the BCI602. Among our patients, high satisfaction with the audiological benefit is communicated; comfort-and improved aesthetics of the Bonebridge with its low profile, especially in comparison to the pre-OP trial-devices, is reported, which is in coherent with the literature [33][34][35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 86%
“…The incidence of post-operative pain also has been reported as relatively low for the BCI601 [32], such complaints were not reported in our cohort, neither for the BCI601 nor for the BCI602. Among our patients, high satisfaction with the audiological benefit is communicated; comfort-and improved aesthetics of the Bonebridge with its low profile, especially in comparison to the pre-OP trial-devices, is reported, which is in coherent with the literature [33][34][35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 86%
“…11 Among our patients, satisfaction with the audiological benefit, comfort, and aesthetics of the BB is high and that corresponds with what is seen in the literature. [3][4][5][6][7] The system also is well regarded for its low profile and aesthetic appearance of the processor, which is greatly appreciated especially by child patients. Most children also report very good results in communication and using the audio processor on a day-to-day basis, while parents especially appreciate the improvement in their children's social interactions and speech development.…”
Section: Discussionmentioning
confidence: 99%
“…Most children also report very good results in communication and using the audio processor on a day-to-day basis, while parents especially appreciate the improvement in their children's social interactions and speech development. 3,6,9 Despite the high levels of satisfaction among BB users, certain complications can occur. A study conducted at the ORL clinic in Vienna during 2012 to 2018 examined 64 patients and found that 6 (9.4%) had postoperative complications requiring examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No major adverse events, defined by the need for revision surgery or explantation, occurred in our study. In the literature only ten major adverse events were described so far: one revision surgery due to headache [ 31 ], one implant removal because of local infection [ 34 ], one explantation due to device failure [ 33 ], one case of sudden loss of hearing benefit [ 31 ], two explantations due to lack of benefit, while these patients were outside of indication criteria [ 25 , 35 ] and four explantations due to wound dehiscence, mainly (3 cases) after implantation in a radical cavity [ 35 ]. According to other studies [ 12 , 23 , 26 , 32 ], our experience has also shown that neither the RS-approach, which is the prefered device localization in patients with radical cavities, nor the sinus and/or dura exposition and compression, or the usage of BCI lifts had any negative influence on patients outcome.…”
Section: Discussionmentioning
confidence: 99%